A Comparative Study of Carbon Nanotubes Synthesized from Co/Zn/Al and Fe/Ni/Al Catalyst - Ezekiel Dixon Dikio (E-Journal of Chemistry)
The catalyst systems Fe/Ni/Al and Co/Zn/Al were synthesized and used in the synthesis of carbon nanotubes. The carbon nanotubes produced were characterized by Field Emission Scanning Electron Microscope (FE-SEM), Energy Dispersive x-ray Spectroscopy (EDS), Raman spectroscopy, Thermogravimetric Analysis (TGA) and Transmission Electron Microscope (TEM). A comparison of the morphological profile of the carbon nanotubes produced from these catalysts indicates the catalyst system Fe/Ni/Al to have produced higher quality carbon nanotubes than the catalyst system Co/Zn/Al.